Gluteal and perineal Hidradenitis Suppurativa: diagnosis and therapeutic management A importância da pesquisa em cirurgia. - Trostchansky, Ivan; Clavijo, Lorena; Garrel, Marcos; Geribaldi, Nicolás; Valiñas, Roberto (Cirugía del Uruguay, 2024)
Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease that affects the apocrine sweat glands and causes inflammatory nodules, abscesses, and painful fistulas in areas such as the armpits, groin, and buttocks. Its impact on patients' quality of life is significant. HS affects 1-4% of the world's population and is associated with factors such as overweight, smoking, and family history. Its pathogenesis is complex, involving inflammation and immune dysfunction. Its diagnosis and treatment are challenging, especially in severe cases. Diagnosis is based on clinical presentation, which is often confused with other skin conditions. It is classified into Hurley stages based on severity. Treatment focuses on controlling symptoms and preventing recurrences. Includes patient education, medical treatment and surgery. The choice of antibiotic therapy depends on the severity and the bacterial strains present. For severe cases, biological therapies are investigated. Surgery, such as simple excision or skin grafts, is effective in controlling the disease. We present a clinical case of a patient with HS, we review the epidemiology, etiopathogenesis and its diagnosis accompanied by the existing therapeutic options